Screen Time and Its Impact on Sleep Patterns in Children: A Multicentric Study in India (International Journal of Environmental Sciences, 2026)
Background: Rapid digitalization has increased exposure of children to screen-based devices such as smartphones, tablets, televisions, and computers. Excessive screen time, particularly during evening hours, may disrupt circadian rhythms and negatively influence sleep patterns.Objective: To assess screen time exposure and its impact on sleep patterns among children aged 2–12 years based on parental reports.Methods: A cross-sectional questionnaire-based study was conducted in four tertiary hospitals across India. Data were collected by medical, dental, and nursing students along with hospital staff. Parents of children aged 2–12 years attending outpatient departments were invited to participate. A structured questionnaire assessed demographic details, average daily screen time, bedtime screen exposure, sleep duration, bedtime routines, and sleep disturbances. Data were analyzed using descriptive statistics and correlation analysis.Results: A total of 400 parents participated. Approximately 64% reported that their children used screens for more than two hours daily. Children with higher screen time showed significantly delayed bedtime, reduced total sleep duration, and increased nighttime awakenings. Screen exposure within one hour before bedtime was associated with increased sleep disturbances and daytime sleepiness.Conclusion: Excessive screen time is strongly associated with altered sleep patterns in children. Limiting evening screen exposure and promoting healthy sleep routines may improve sleep quality and overall well-being in children.